Corrosion Retardation of Mild Steel Electrodeposited with 4-hydroxybenzalaniline in 0.5 M NaCl - Athirah Dzolin, Syaidah; Bahron, Hadariah; Yusairie Mohd, Yusairie; Zakiah Nor Hashim, Nor (International Journal of Engineering and Technology, 2018)
The synthesis of a Schiff base, 4-hydroxybenzalaniline (4-HB) was carried out via condensation reaction giving 81.7% yield. 4-HB was characterized via physicochemical and spectroscopic techniques namely melting point, microelemental analysis (C, H and N), Proton Nuclear Magnetic Resonance (1H NMR) and Infrared (IR) spectroscopy. The characteristic ï®(C=N) peak was observed at 1613 cm-1 and the ï¤(OH) at 10.15 ppm. Cyclic voltammetry (CV) and chronoamperometry (CA) techniques were employed to electrodeposit 4-HB on mild steel with 0.1 M inhibitor concentration in 0.3 M NaOH.Â The formation of a yellow imine film was observed on the mild steel. The corrosion behavior of uncoated and coated mild steel was investigated using Tafel Extrapolation Method (TEM) and Electrochemical Impedance Spectroscopy (EIS) in 0.5 M NaCl corrosion medium. The coated mild steel showed more superior corrosion resistance than the uncoated one.Â The mild steel coated with 4-HB through CA technique at potential +1.50 V revealed the highest inhibition efficiencies of 97.71 % and 96.79 % for EIS and TEM investigations, respectively, indicating a good surface coverage. The Schiff base revealed potent organic corrosion inhibition activity and has a high potential for commercialization.Â Â